MISCONCEPTION REMEDIATION OF ATOMIC ORBITAL, MOLECULAR ORBITAL, AND HIBRIDIZIATION CONCEPTS BY COMPUTER ASISSTED INSTRUCTION WITH ANIMATION AND SIMULATION MODEL - Sri Mursiti; Dewi Selvia Fardhyanti; Edy Cahyono; Sudarmin Sudarmin (Indonesian Journal of Chemistry, 2006)
The research of Computer Asissted Instruction with animation and simulation was used to misconception remediation of atomic orbital, molecular orbital, and hibridiziation concepts. The applicated instruction model was focused on concept approach with macromedia flash player and power point programme. The subject of this research were the 2nd semestre students of Chemistry Department. The data were collected by using of true-false pre-test and post- test followed by the reason of its. The analysis reveals that the Computer Asissted Instruction with animation and simulation model increased the understanding of atomic orbital, molecular orbital, and hibridiziation concepts or remediation of concepts missconception, shown by the significant score gained between before and after the implementation of Computer Asissted Instruction with animation and simulation model. The instruction model developed the students's generic skills too.